Indigenous Land in Brazil: Analysis of Federal Supreme Court Trials - Folena de Oliveria, Jorge Rubem (2019)
The article was written based on an investigation that analyzes various trials conducted by the Federal Supreme Court on indigenous land issues in Brazil, such as the case of the Raposa Serra do Sol reserve. The methodology implemented was the examination of the votes and decisions of the judges of the Federal Supreme Court in the trials related to these issues. This investigation verified the behavior of an indifferent Federal Supreme Court in relation to the Brazilian indigenous people, in the face of the cruelty with which they were evicted and expelled from their ancestral lands, through practices carried out by invaders and by the State itself. It can be said that the behavior of the members of the Federal Supreme Court is a reflection of a society so accustomed to centuries of exploitation. This society has become incapable of expressing repulsion when it comes to the suffering of others; thereby, acts of injustice against fellow human beings are passively accepted.